The relationship of Parental Pain Catastrophizing with Parents Reports of Children’s Anxiety, Depression and Headache Severity - Akbarzadeh, Ghazaleh; Daniali, Hojat; Javadzadeh, Mohsen; Caes, Line; Ranjbar, Seyran; Habibi, Mojtaba (Iranian Journal of Child Neurology, 2018)
Abstract: Introduction: Parental pain catastrophizing is a construct which is recognized to have a significant impact on experience and report of pain in both children and parents. The main aim of the current research is to investigate the probable relationship of parental pain catastrophizing with the parent reports of children’s anxiety, depression and headache severity amongst Iranian parents of children with chronic or recurrent headache. Method: In this study 212 parents (120 mothers and 92 fathers) of children with chronic or recurrent pain participated and completed the Pain Catastrophizing Scale; Numeric Pain Rating Scale, asking for the average of pain severity in last three months before the research, and the Anxiety and Depression subscales of the Children Behavioral Check List. Findings: The mean age of parents was 35.41 (SD= 5.58) and the mean age of children were 9.83 (SD= 2.77). A total of 72 girls and 60 boys participated in this study with a mean pain severity for headache in last three months before the research of 4.99 (SD=2.63). Probable sex differences according to pain catastrophizing, pain severity, anxiety and depression were assessed. In the next step, the predictability of pain severity from parental pain catastrophizing was evaluated. Results indicated a significant relationship in maternal pain catastrophizing and estimates of pain intensity by mothers. Conclusions: These findings represent the importance of parent’s cognitive factors affecting their reports of their children’s pain and related emotional disturbances.